2023
DOI: 10.1021/acsami.3c14281
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Flexible Pressure Sensors with Hybrid Microstructures Similar to Volcano Sponge

Yilin Zhao,
Xiao Lei,
Ziran Zeng
et al.

Abstract: Preparing hybrid microstructures on flexible substrates is a crucial approach to achieving highly sensitive flexible pressure sensors. However, the preparation of hybrid microstructures on soft materials often faces complex, time-consuming, and costly problems, which hampers the advancement of highly sensitive flexible sensors. Herein, based on a 3D-printing template and a household microwave oven, a simple, green, and one-step microwave irradiation process using glucose porogen is applied to develop a flexibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Due to the controllable preparation of the hollow graphene microspheres, the variation in the relative current versus pressure curves from device to device is negligible (Figure S15). Moreover, a comparison of the pressure-sensing performance between the as-prepared HGP-film-based sensor and the research of other common micropattern-based sensors is shown in Figure h, demonstrating that this work achieves a superior sensitivity for a wide linear range. ,,, …”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Due to the controllable preparation of the hollow graphene microspheres, the variation in the relative current versus pressure curves from device to device is negligible (Figure S15). Moreover, a comparison of the pressure-sensing performance between the as-prepared HGP-film-based sensor and the research of other common micropattern-based sensors is shown in Figure h, demonstrating that this work achieves a superior sensitivity for a wide linear range. ,,, …”
Section: Resultsmentioning
confidence: 84%
“…31,32 For example, Zhao fabricated a pressure sensor based on a hybrid structure through a one-step microwave irradiation process, showing a high sensitivity of 611.85 kPa −1 . 33 Therefore, developing a facile and low-cost method to achieve random surface patterns and tunable porous bulk structure design, which shows great potential in synergistically optimizing the performance of the sensors, is of great potential.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the sensors, flexible pressure sensors are popular due to their advantages such as flexibility, conformal attachment, and high sensitivity, showing great applications in wearable devices, 1,2 electronic skin, 3,4 human–computer interaction, 5,6 medical and healthcare, 7,8 etc. By far, various materials including polyimide (PI), 9,10 polyethylene terephthalate (PET), 11,12 polydimethylsiloxane (PDMS), 13–15 polyurethane (PU), 16,17 etc. , have been exploited as substrates to develop flexible pressure sensors.…”
Section: Introductionmentioning
confidence: 99%